2005
DOI: 10.1016/j.clpt.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the genotype on the pharmacokinetics, pharmacodynamics, and drug interactions of intravenous lorazepam in healthy volunteers

Abstract: Our results suggest that the UGT2B15*2 polymorphism is a major determinant of interindividual variability with respect to the pharmacokinetics and pharmacodynamics of lorazepam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
59
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 18 publications
3
59
0
3
Order By: Relevance
“…Hepatic expression of UGT shows little interindividual variation, as opposed to the high interindividual variability found in the gastrointestinal tract (Strassburg et al, 1998(Strassburg et al, , 2000, further accentuated by the differential enzyme expression within different segments of the gastrointestinal tract (Strassburg et al, 1998(Strassburg et al, , 2000Antonio et al, 2003;Basu et al, 2004). Genetic polymorphisms have been described for several UGT, and some of them have been associated with interindividual variations in drug effect (Chung et al, 2005) and toxicity (Marsh and McLeod, 2004;Massacesi et al, 2006). Therefore, the identification of specific enzymes involved in the metabolism of a drug is important.…”
mentioning
confidence: 99%
“…Hepatic expression of UGT shows little interindividual variation, as opposed to the high interindividual variability found in the gastrointestinal tract (Strassburg et al, 1998(Strassburg et al, , 2000, further accentuated by the differential enzyme expression within different segments of the gastrointestinal tract (Strassburg et al, 1998(Strassburg et al, , 2000Antonio et al, 2003;Basu et al, 2004). Genetic polymorphisms have been described for several UGT, and some of them have been associated with interindividual variations in drug effect (Chung et al, 2005) and toxicity (Marsh and McLeod, 2004;Massacesi et al, 2006). Therefore, the identification of specific enzymes involved in the metabolism of a drug is important.…”
mentioning
confidence: 99%
“…Rifampin increases clearance of a number of antiretroviral agents via this mechanism (2, 3). Furthermore, rifampin also induces phase II enzymes, such as UDPglucuronosyl transferase, which has been described to act in vitro and in vivo (5,8,21), and therefore has potential to affect the pharmacokinetics of raltegravir.…”
mentioning
confidence: 99%
“…18 All 4 studies showed that valproic acid cotreatment inhibited the metabolism of lorazepam, as indicated by an observed decrease in either lorazepam glucuronide formation clearance 17,18 or the metabolite AUC ratio. 9,19 With regard to elimination, a decrease in plasma clearance of lorazepam was observed in all 4 studies. 9,[17][18][19] Some limitations in the interpretation of data from clinical drug interaction studies deserve mention.…”
Section: Discussionmentioning
confidence: 99%
“…9,19 With regard to elimination, a decrease in plasma clearance of lorazepam was observed in all 4 studies. 9,[17][18][19] Some limitations in the interpretation of data from clinical drug interaction studies deserve mention. For example, in addition to UGT induction or inhibition, formation clearance may also be affected by clearance or AUC of the parent drug and other drug-metabolizing enzymes or transport proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation